Problems of tourism business development in Ukraine: a regional aspect - Perehuda, Yuliia (Management and Entrepreneurship: Trends of Development, 2025)
The article is devoted to the development of new scientific solutions to identify key challenges related to the tourism business in various parts of Ukraine. It also explores potential ways to solve the problems of tourism entrepreneurship development in the regions of the country amid rising military risks, as well as the transition to a post-industrial development model and acceleration of European integration processes. The research identifies the main trends in tourism development across the country and Ukrainian areas since 2014. Besides, it reveals the benefits of tourist business development for the country as a whole and the individual Ukrainian regions. The article aims to develop a set of measures to foster tourism entrepreneurship in the regions of Ukraine during the ongoing war and after the end of hostilities in the country, based on the analysis of how the tourism sphere has functioned across Ukrainian regions since 2014, as well as the identification of the key problems that the regional tourism business of the state faces. Methodology: a set of general and specialized methods was used at the empirical and theoretical levels. These include: literary analysis to examine foreign and Ukrainian scientific contributions in the field of regional tourism business; historical and comparative assessment to identify trends and features of tourism business development across regions of Ukraine and in the country as a whole since 2014; comparative method to determine the key problems that prevent the realization of tourism business potential in the regions of Ukraine; inductions and deductions to identify the benefits that the tourism business development in the regions brings to the state, individual regions, and the population of the country (regions of the country); logical generalization and scientific abstraction to formulate a set of measures for the tourism entrepreneurship fostering in Ukrainian regions during the war and after the end of hostilities in the country; methods of systematization, grouping and logical generalization to organize information, develop conclusions and scientific proposals of the article. The article employs system-functional, historical, and systemic approaches to reveal and address the problems of tourism entrepreneurship development in Ukraine's regions during the ongoing war and in the aftermath of the country's hostilities. Results: a comprehensive set of tourism entrepreneurship development measures in the regions of Ukraine during wartime and after the cessation of hostilities has been proposed.JEL Classification: L20, L80, L84